A randomized, placebo-controlled trial of sustained-release dextroamphetamine for treatment of methamphetamine addiction - Galloway, G P; Buscemi, R; Coyle, J R; Flower, K; Siegrist, J D; Fiske, L A; Baggott, M J; Li, L; Polcin, D; Chen, C Y A; Mendelson, J (Clinical pharmacology and therapeutics, 2011)
Sixty treatment-seeking individuals with methamphetamine (MA) dependence entered a randomized, placebo-controlled, double-blind clinical trial of oral dextroamphetamine (d-AMP) as a replacement therapy for MA dependence. The subjects took 60 mg sustained-release d-AMP for 8 weeks, during which time they received eight 50-min sessions of individual psychotherapy. Adverse events and urine toxicology for MA were assessed two times a week. There were no serious adverse events. Urine samples containing <1,000 ng/ml of MA were classified as negative for MA. The MA-negative scores in the d-AMP group (3.1 ± SD 4.6) were no higher than those in the placebo group (3.3 ± SD 5.3; P > 0.05). However, withdrawal and craving scores were significantly lower in the d-AMP group (P < 0.05 for both). Although subjects taking d-AMP did not reduce their use of MA, the significant reductions observed in withdrawal and craving scores in this group support the need for further exploration of d-AMP as a pharmacologic intervention for MA dependence, possibly at higher doses.